Internet Commerce As a Possible Direction for the Development of Entrepreneurship Supply Chain and Information Management - V. Terentyeva, Tatyana; V. Nedoluzhko, Olga; G. Shumik, Ekaterina; S. Kostenko, Kristina (ExcelingTech, 2020)
Information and communications technology in supply chain management has enabled corporations to use offshore facilities for outsourcing commercial activities. One of the current trends in the global economic space is the formation of an information economy that allows fulfilling the requirements for the interaction organization between business entities at a high organizational level. At the same time, the traditional economy is significantly lagging behind in the development of new economic trends such as digitalization, supply chain and information management, which necessitates to create effective measures aimed at developing the economic information space: in particular, the Internet entrepreneurship supply chain management. To solve this problem, it is proposed to use a combination of quantitative and qualitative methods, including test analysis method, logical-structural and causal analysis, as well as synthesis of literature, strategic analysis method, content analysis, applied economic and statistical methods, and sociological survey. Using these methods allowed determining the set of factors affecting the growth and development of the Internet entrepreneurship supply chain. We classified e-commerce models according to various criteria, formed different directions of the impact of government regulation on the e-commerce market and information management in the supply chain system. The identification of factors holding back the development of e-commerce made it possible to determine the nature of their negative impact on the development of the Internet entrepreneurship supply chain and to give some recommendations on improving the efficiency of state regulation of this sphere and ensuring its greater attractiveness in the minds of consumers. Application of the obtained results will make it possible to prepare regulatory and program documents in the field of state regulation of the Internet entrepreneurship supply chain and determine possible directions for its development in the future.